Analytical, numerical and experimental assessment of vibration performance in timber floors. (1st August 2018) - Casagrande, Daniele; Giongo, Ivan; Pederzolli, Federico; Franciosi, Alessandro; Piazza, Maurizio
Highlights: The vibration performance of two timber floors is assessed. Numerical modelling is used to predict the dynamic behaviour of the two floors. Experimental tests were performed both in laboratory and on-site. Comparison between the different analysis models is presented. Abstract: The assessment of the dynamic properties and vibration performance of two full-scale timber floor specimens is presented. The specimen set comprised a Timber-Concrete Composite floor and a Cross Laminated Timber floor. The floors, which are characterized by the same length and mass, are located in two separate five-storey timber buildings constructed in the urban area of Trento (Italy). The assessment was conducted by adopting analytical and numerical methods as well as by performing onsite experimental tests. Mock up samples of the floor specimens were also made and tested in laboratory. Multiple analytical methods that are available in literature were evaluated and compared. The Vibration Dose Value (VDV) method, as proposed by ISO 10137 and BS 6472, was used as reference method for the numerical modelling and the laboratory testing. To determine the VDV, loading associated to human walking was simulated. Dynamic identification tests, where the floors were excited by a modal hammer, were also performed in order to investigate the dynamic properties (i.e. natural frequencies, damping and mode shapes) of the floors. Discussion on the vibration performance of the timber floor typologies studied herein and on the effectiveness of the different assessment approaches (i.e. analytical, numerical and experimental) is provided.